Companion dog acquisition and mental well-being: a community-based three-arm controlled study - Powell, Lauren (BMC Public Health, 2019)
BACKGROUND: Dog ownership is suggested to improve mental well-being, although empirical evidence among community dog owners is limited. This study examined changes in human mental well-being following dog acquisition, including four measures: loneliness, positive and negative affect, and psychological distress. METHODS: We conducted an eight-month controlled study involving three groups (n = 71): 17 acquired a dog within 1 month of baseline (dog acquisition); 29 delayed dog acquisition until study completion (lagged control); and 25 had no intentions of acquiring a dog (community control). All participants completed the UCLA Loneliness Scale (possible scores 0–60), Positive and Negative Affect Schedule and Kessler10 at baseline, three-months and eight-months. We used repeated measures ANCOVAs to analyse data with owner age and sex included as covariates. Post-hoc tests were performed for significant effects (p < 0.05). RESULTS: There was a statistically significant group by time interaction for loneliness (p = 0.03), with an estimated reduction of 8.41 units (95% CI -16.57, − 0.26) from baseline to three-months and 7.12 (95% CI -12.55, − 1.69) from baseline to eight-months in the dog acquisition group. The group by time interaction for positive affect was also significant (p = 0.03), although there was no change in the dog acquisition group. CONCLUSIONS: Companion dog acquisition may reduce loneliness among community dog owners. Our study provides useful direction for future larger trials on the effects of dog ownership on human mental well-being. TRIAL REGISTRATION: This trial was retrospectively registered on 5th July 2017 with the Australian New Zealand Clinical Trials Registry (ACTRN12617000967381).